Transcranial direct current stimulation for balance rehabilitation in neurological disorders: A systematic review and meta-analysis - Beretta, Victor Spiandor [UNESP] (2022)
Postural instability is common in neurological diseases. Although transcranial direct current stimulation (tDCS) seems to be a promising complementary therapy, emerging evidence indicates mixed results and protocols’ characteristics. We conducted a systematic review and meta-analysis on PubMed, EMBASE, Scopus, and Web of Science to synthesize key findings of the effectiveness of single and multiple sessions of tDCS alone and combined with other interventions on balance in adults with neurological disorders. Thirty-seven studies were included in the systematic review and 33 in the meta-analysis. The reviewed studies did not personalize the stimulation protocol to individual needs/characteristics. A random-effects meta-analysis indicated that tDCS alone (SMD = −0.44; 95%CI = −0.69/−0.19; p < 0.001) and combined with another intervention (SMD = −0.31; 95%CI = −0.51/−0.11; p = 0.002) improved balance in adults with neurological disorders (small to moderate effect sizes). Balance improvements were evidenced regardless of the number of sessions and targeted area. In summary, tDCS is a promising therapy for balance rehabilitation in adults with neurological disorders. However, further clinical trials should identify factors that influence responsiveness to tDCS for a more tailored approach, which may optimize the clinical use of tDCS.